Next-Generation Sequencing Reveals the First Complete Genome Sequence of Cowpea aphid-borne mosaic virus from Uganda - Mbeyagala, E.K.; Tukamuhabwe, Phineas; Bisikwa, J.; Holton, T.; Mukasa, S.B. (American Society for Microbiology, 2018)
We present here the first complete genome sequence of Cowpea aphid-borne mosaic virus (CABMV) isolated from cowpea in Uganda and compare it with five CABMV complete genome sequences from Brazil (2), India (2), and Zimbabwe (1). It most resembled the genomes of two Brazilian isolates (MG-Avr and BR1) and one Indian isolate (RR3).